Efektivitas Penggunaan Model Pembelajaran Inquiry Pada Materi Teorema Phytagoras Terhadap Siswa SMPN 2 Sungai Penuh - Hatria, Jihan Dwi; Vrasetya, Arshinta; Yulia, Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This research aims to determine the role of guided inquiry in students’ conceptual understanding in learning the Pythagorean Theorem, through a Student Activity Sheet based on the guided inquiry learning model. This research used a qualitative descriptive research method, which was carried out in class VIII F of SMP Negeri 2 Sungai Full. The data collection techniques used are documentation, observation and written tests. The data obtained in this research was analyzed using data triangulation techniques. The research results show That Guided Inquiry plays a role in helping students to understand the concept of the Pythagorean theorem formula, through several learning stages. In learning that uses guided inquiry, students are guided in a structured manner to understand the Pythagorean theorem formula By finding it yourself and being facilitated by the teacher. In addition, student learning results show that the average score obtained is above the Minimum Completeness Criteria score for mathematics subjects of 65.